2017
DOI: 10.1107/s2056989016019538
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 2-oxo-2H-chromen-3-yl 4-chlorobenzoate and Hirshfeld surface analysis

Abstract: In the title compound, C16H9ClO4, the dihedral angle between the coumarin ring system [maximum deviation = 0.023 (1) Å] and the benzene ring is 73.95 (8)°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…tuents at the 7 position (Ramasubbu et al, 1982;Gnanaguru et al, 1985;Parveen et al, 2011;Ji et al, 2014Ji et al, , 2017. In these structures and those of meta-substituted coumarin esters (Abou et al, 2013;Bibila Mayaya Bisseyou et al, 2013;Yu et al, 2014;Gomes et al, 2016;Ziki et al, 2016Ziki et al, , 2017, the pyrone rings show three long (in the range 1.37-1.46 Å ) and one short (1.32-1.34 Å ) C-C distances, suggesting that the electronic density is preferentially located in the short C-C bond at the pyrone ring. This pattern is clearly repeated for (I) with C2-C3 = 1.332 (5) Å , while C1-C2 = 1.451 (5), C3-C4 = 1.434 (4) and C4-C5 = 1.399 (4) Å .…”
Section: Database Surveymentioning
confidence: 88%
“…tuents at the 7 position (Ramasubbu et al, 1982;Gnanaguru et al, 1985;Parveen et al, 2011;Ji et al, 2014Ji et al, , 2017. In these structures and those of meta-substituted coumarin esters (Abou et al, 2013;Bibila Mayaya Bisseyou et al, 2013;Yu et al, 2014;Gomes et al, 2016;Ziki et al, 2016Ziki et al, , 2017, the pyrone rings show three long (in the range 1.37-1.46 Å ) and one short (1.32-1.34 Å ) C-C distances, suggesting that the electronic density is preferentially located in the short C-C bond at the pyrone ring. This pattern is clearly repeated for (I) with C2-C3 = 1.332 (5) Å , while C1-C2 = 1.451 (5), C3-C4 = 1.434 (4) and C4-C5 = 1.399 (4) Å .…”
Section: Database Surveymentioning
confidence: 88%
“…A CSD search (Web CSD version 5.39; March 9, 2018; Groom et al, 2016) found five coumarin ester structures with substituents at the 7 positions (Ramasubbu et al,1982;Gnanaguru et al, 1985;Parveen et al, 2011;Ji et al, 2014Ji et al, , 2017. In these structures and those of meta-substituted coumarin esters (Abou et al, 2012(Abou et al, , 2013Bibila Mayaya Bisseyou et al, 2013;Yu et al, 2014;Gomes et al, 2016;Ziki et al, 2016Ziki et al, , 2017 Hydrogen-bond geometry (Å , ).…”
Section: Database Surveymentioning
confidence: 99%
“…The C3-C2 [1.3332 (18) Å ] and C2-C1 [1.4553 (19) Å ] bond lengths are slightly shorter and longer, respectively, than those expected for a C ar -C ar bond. This suggests that the electron density is preferentially located in the C2-C3 bond at the pyrone ring, as seen in other coumarin derivatives (Gomes et al, 2016;Ziki et al, 2017).…”
Section: Structure Descriptionmentioning
confidence: 75%